2021
DOI: 10.1002/eat.23659
|View full text |Cite
|
Sign up to set email alerts
|

Secondary effects of body dissatisfaction interventions on adolescent depressive symptoms: A meta‐analysis

Abstract: Objective: Depression is a leading cause of disability among adolescents, yet existing treatments are variably effective, suggesting needs to identify novel intervention targets. Body dissatisfaction (BD) may be a promising, but understudied, target: BD is common among adolescents; prospectively associated with future depression; and modifiable through intervention. BD interventions are typically evaluated in terms of impacts on eating disorders, but many trials also measure depression-related secondary outcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…In line with calls for more interventions to target shared risk factors (Ahuvia et al, 2022;Puccio et al, 2016;Becker et al, 2014), Project Body Neutrality targets transdiagnostically-relevant risk factors connected to depression and EDs. Its single-session format recognizes the dropout characteristic of longer-term interventions (Fleming et al, 2018;Clough et al, 2022), and capitalizes on the changes that can be accomplished in a short timeframe (Schleider et al, 2020a).…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with calls for more interventions to target shared risk factors (Ahuvia et al, 2022;Puccio et al, 2016;Becker et al, 2014), Project Body Neutrality targets transdiagnostically-relevant risk factors connected to depression and EDs. Its single-session format recognizes the dropout characteristic of longer-term interventions (Fleming et al, 2018;Clough et al, 2022), and capitalizes on the changes that can be accomplished in a short timeframe (Schleider et al, 2020a).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…A systematic review of 26 ED prevention and early intervention trials found that 42% significantly reduced depression symptoms, in addition to eating pathology (Rodgers & Paxton, 2014). Additionally, a meta-analysis of 13 RCTs found that interventions designed to reduce adolescent body dissatisfaction significantly reduced depression symptoms, as well (Ahuvia et al, 2022). These studies suggest that interventions mitigating ED pathology can reduce depression symptoms, even when depression is not intentionally targeted.…”
Section: Utility Of Targeting Both Depression and Edsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Overspecialization of EDs also makes it more difficult to identify transdiagnostic mechanisms that account for comorbidity with other disorders, impeding progress on both EDs and other disorders. 15 For instance, one review found that body image interventions generate improvements in depression of the same magnitude as treatments specifically targeting depression, 35 suggesting that other fields could also benefit from dialogue with ED researchers.…”
Section: The Danger Of False Assumptionsmentioning
confidence: 99%
“…Mindfulness is increasingly investigated within eating disorder prevention and early intervention (Beccia et al, 2018 ). Examining processes through which mindfulness affects risk can support more efficient and effective prevention of eating disorders and other psychiatric conditions (Ahuvia et al, 2022 ). Emotion regulation is commonly proposed to be a mechanism of mindfulness (e.g., Chiesa et al, 2014 ; Hölzel et al, 2011 ; Roemer et al, 2015 ; Vanzhula & Levinson, 2020 ); however, few longitudinal studies have examined emotion regulation as a mediator.…”
Section: Introductionmentioning
confidence: 99%